Edukasi dan Skrining Kesehatan Lansia dengan Penyakit Tidak Menular di Kelurahan Pauh Kota Padang - Rika Sabri; Meri Neherta; Dewi Eka Puteri; Deswita Deswita; Elvi Oktarina; Devia Puteri Lenggogeni; Ira Mulyasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Non-communicable diseases (NCDs) are dangerous diseases and result in death. The problems found by partners are the low coverage of NCD screening targets, access to health services and the absence of an integrated services centre for the elderly in the targetted area, which impacts NCD monitoring not being carried out. Community service activities aimed to prevent and suppress NCD cases, especially for older people in vulnerable groups. The solution was to detect NCD and provide education and counselling for older people with NCD problems. The community service partner was the Public Health Center. The method of implementing activities was health screening (measuring height and weight, blood pressure, blood sugar, cholesterol and uric acid), providing health education about hypertension and diabetes mellitus and health counselling for those indicated by NCDs in Pauh sub-District, Padang, West Sumatra, Indonesia. The screening results found 15 healthy older people, 13 people with hypertension, ten people with diabetes, nine people with rheumatism, and seven people with high cholesterol. The results of education and counselling found an increase in knowledge by 16.69 points—follow-up plans by partners to form elderly health centres.